2011
DOI: 10.1016/j.neuroimage.2010.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diffusion tensor imaging detects white matter degeneration in the spinal cord of a mouse model of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by selective degeneration of motor neurons. Here we examine the ability of magnetic resonance imaging (MRI) to measure axonal degeneration in the lumbar spinal cord of the SOD1 mouse model of ALS. Diffusion tensor imaging (DTI) was successful in detecting axonal spinal cord damage in vivo. Fractional anisotropy (FA) values were reduced exclusively in the ventral white matter tracts of the lumbar spinal cord of ALS-affected SOD1 mice compared to wild-type lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…This is in agreement with previous studies that reported alterations on MRI only after the 12 th week in this ALS murine model [14]. However, TEM showed modifications in motor neurons of G93A-SOD1 spinal cord already at 10 weeks of age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous studies that reported alterations on MRI only after the 12 th week in this ALS murine model [14]. However, TEM showed modifications in motor neurons of G93A-SOD1 spinal cord already at 10 weeks of age.…”
Section: Discussionsupporting
confidence: 93%
“…As expected [14,30], FA and AD are reduced as a consequence of the fiber disorganization shown by our TEM results. The unexpected reduction of MD, detected with all the three protocols, could be explained by the vacuolization phenomena observed in G93A-SOD1 motor neuron by our histology and TEM as well as in previous studies [66]; indeed vacuolization is associated with diffusivity reduction in other neurodegenerative pathologies such as Creutzfeldt-Jakob disease [67,68].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Budde et al revealed that axial diffusion in the ventrolateral white matter in the experimental autoimmune encephalomyelitis (EAE) mouse model was significantly negatively correlated with the EAE clinical score and was significantly lower in mice with severe EAE than in mice with moderate EAE [45]. In the ventral white matter tracts of the spinal cord of ALS-affected mice, the diffusion values altered with disease progression [46,47]. In an SCI study, Kim et al identified the spared, normal ventrolateral white matter by the hyperacute axial diffusion 3 h after injury, and a histological analysis performed 14 days later showed a good correlation with the spinal contusion injury [48].…”
Section: Dti Of the Spinal Cordmentioning
confidence: 99%
“…To investigate potential subtle changes, it is crucial to obtain microstructure information of tissues throughout the length of the spinal cord. Current methods generally perform multiple investigations in laboratory by imaging the entire spinal cord on small animals (Ellingson et al, 2008;Cohen-Adad et al, 2011;Underwood et al, 2011). Nevertheless, the results demonstrated on the animals may not be same to the humans.…”
Section: Introductionmentioning
confidence: 99%